ANALYSIS OF THE UTILIZATION OF TRADITIONAL HOPONG DANCE IN TEACHING RHYTHMIC ACTIVITIES IN SCHOOLS - Arif, Yudabbirul; Barlian, Eri; Gusril; Oktafiranda, Nadya Dwi (Gladi : Jurnal Ilmu Keolahragaan, 2024)
This study aims to analyze the utilization of the traditional Hopong dance as a medium for teaching rhythmic activities to seventh-grade students at SMP Negeri 6 Kupang Barat. Originating from the Helong tribe in East Nusa Tenggara, the Hopong dance carries profound cultural and philosophical values. Its movements combine elements of aesthetics, rhythm, and expression, which are relevant to the development of rhythmic activities in physical education. This research employs a naturalistic qualitative descriptive method, with data collected through observation, interviews, and documentation. The research subjects include physical education teachers and seventh-grade students. The data were analyzed to identify the role of basic Hopong dance movements in supporting students' physical abilities, such as muscle strength, balance, flexibility, and agility, as well as their impact on understanding local culture. The results show that the use of the Hopong dance as a teaching medium for rhythmic activities significantly benefits students, both in physical aspects and in their appreciation of regional culture. Students demonstrated high enthusiasm during the learning process, creating a fun and supportive atmosphere for creativity. This study recommends that the Hopong dance be more widely used as a teaching medium to preserve cultural heritage while enhancing students' skills